Analyzing the Adoption of Recent IT Technologies in Undergraduate Engineering Project Course - Adamuthe, Amol C.; Mane, Sandeep U. (Journal of Engineering Education Transformations, 2021)
Outcome-based professional education processes are a new standard for all stakeholders and knowledge economy. Majority of the time the IT services/consulting industry demands graduates who shall be billable from day one of joining the enterprise. According to the National Employability Report Engineers 2019, only 3% of engineers possess new-age skills in areas such as AI, data analytics and mobile technologies. Academic project works shall be seen in the light of aforesaid observations and therefore suggests treating this as an opportunity to initiate undergraduates to more hands-on experiential learning considering the advancements in technology and market need. The objective of this paper is to identify the gap between the needs of the market/job trends and undergraduate CS/IT student projects areas. The second objective is to identify the factors affecting the project selection process. Our empirical study in general spanning over seven Engineering Institutes in western Maharashtra. The statistical data is collected from a controlled group of 4000 students. The data consists of project topics completed by students in the last nine years (from the year 2011 to the year 2019). Two indicators are used to understand the IT market. First, Gartner strategic technologies present the worldwide trend of technologies. Second, student project areas are compared with job trends in India. The student’s feedback on technology adoption theory presents the challenges in adoption of recent IT technologies in academic projects. 62% of students have reported unavailability of resources at the institute to encourage the adoption of the recent technologies. The student’s perception about the adoption of recent technologies needs to change.